EVALUASI KESESUAIAN ERGONOMI ANTARA FASILITAS KAMAR MANDI DENGAN FISIOLOGI DAN ANTROPOMETRI LANSIA - Mohammad Rusda Habib (The Indonesian Journal of Occupational Safety and Health, 2017)
Bathroom was major personal hygiene facilities for elderly in Hargo Dedali Nursing HomeSurabaya. Elderly bathroom design need to consider with ergonomic factor for elderly to minimize of falling. The purpose of this study was describing suitability of bathroom facilities ergonomic according physiological and elderly anthropometric factors in the Nursing Home. This study was conducted with cross-sectional design with descriptive analysis approach. Observations and measurements were taken at the place and variables were personal hygiene facilities, physiological, and elderly anthropometric. Data that used were primary data based on observations and interviews and secondary data drawn from the place. The result showed that elderly bathroom ergonomic design were height of closet 42,5 ±2,609 cm; height   of bathing tub 68,65±6,492 cm; height of water cock 90,09±6,067 cm; volume  of water dipper1000 ml; height of hand rail 80,09±6,067 cm; diameter of handful 4,6±0,2 cm at persentile5th; slope of floor ≥ 40  with rough floor texture; lenght of doorleaf with handle 16 cm; lighting during the day and the night for more than 100 lux. The conclusion was that not all bathroom facilities at nursing home eligible for elderly. Advice that can be given were the bathroom need adjustment size with ergonomic values obtained and necessary uniformity in design was not only space but also uniformity in size according to the physiological and elderly anthropometric who can access to bathroom independently. Keywords: ergonomics, bathroom, elderly